PEMODELAN RANCANGAN WEBSITE ├óΓé¼╦£MITRA UTAMA TEKNIK├óΓé¼Γäó MENGGUNAKAN STRUKTUR NAVIGASI DAN UML - -, Suharni; Susilowati, Eel; Harlina, Masimbangan Sabarina; Herawati, Masimbangan Susana; Raharjo, Dimas Budi (JURNAL REKAYASA INFORMASI, 2025)
Mitra Utama Teknik is a business engaged in AC service. The service ordering system at Mitra Utama Teknik still uses WhatsApp (WA) or telephone, so the Administration Section for ordering services at Mitra Utama Teknik has difficulty in managing AC service order data. Sometimes the data is missed, some are not recorded, and the order of incoming data is not regular with the service order. In addition, by using WhatsApp media, customers are limited to the community on WA. Mitra Utama Teknik hopes to be able to fix the problems in the administration section of AC service regularly and that its service information can reach a wider range of customers. The initial step to achieve the goals and expectations, the researcher wants to help by creating a website design model. The models that will be used to create the Mitra Teknik Utama website are Navigation Structure and UML (Unified Modeling Language) with diagrams consisting of Usecase diagrams, activity diagrams, and class diagrams. The results of the Navigation and UML structure design can be used as a reference by system developers to be implemented into a website that can help the Mitra Teknik Utama AC service business activities in achieving their goals.